The Components of the Iraqi Countryside and its Impact on the Development of Rural Tourism: Komponen Pedesaan Irak dan Dampaknya terhadap Pengembangan Pariwisata Pedesaan - Zainab Ibrahim Kazem; Ass. Prof. Dr. Zainab Sadiq Mustafa (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Rural regions in Iraq play an essential role in national livelihoods, agriculture, and community sustainability, yet they face multiple environmental and socioeconomic challenges. Specific Background: Persistent water scarcity, limited infrastructure, and unequal access to public services continue to affect the living conditions of rural populations. These issues are further intensified by climate change, desertification, and governance constraints. Knowledge Gap: Although several international reports and studies address individual aspects of rural development in Iraq, a comprehensive perspective that integrates environmental pressures, social inequalities, and development limitations remains limited. Aims: This study examines the structural challenges affecting rural communities in Iraq, focusing on water resources, infrastructure, rural livelihoods, and access to services. Results: The analysis shows that water scarcity, weak rural infrastructure, and socioeconomic disparities significantly shape rural living conditions and limit development opportunities. These factors interact with environmental changes and institutional constraints, creating persistent barriers to sustainable rural development. Novelty: The article synthesizes diverse sources to present an integrated overview of environmental and social challenges affecting rural areas in Iraq. Implications: Understanding these interconnected challenges can support policymakers and development institutions in designing more comprehensive strategies to improve rural livelihoods and resource management. Keywords: Rural Development, Water Scarcity, Rural Livelihoods, Climate Change, Iraq Key Findings Highlights Rural communities face interconnected environmental and socioeconomic challenges Water scarcity and infrastructure limitations shape rural living conditions Institutional and environmental pressures constrain sustainable development